Beginnings of the Transatlantic security partnership: Outbreak of the Cold War and the establishment of the Atlantic Alliance (Economic and Political Thought, 2019)
The aim of this article was to show the origin of the Transatlantic securitypartnership and the process that led to the creation of NATO in 1949.The article draws attention to the aggravation of East–West relations, whichresulted in the outbreak of the Cold War and the transformation of the USpolicy after the Second World War. The worsening of the international situationalso led to the initiation of Western European countries’ cooperationand integration in the area of security and defence. The outbreak of the ColdWar was the result of a significant transformation of international relationsconsisting mainly in the emergence of two superpowers, i.e. the United Statesand the Soviet Union. Due to Moscow’s expansionist policy, after 1945 theUnited States abandoned its traditional isolationist policy in favour of activeinvolvement in Europe’s problems. The initiatives adopted in 1947 followingthe new American approach, i.e. the Truman Doctrine, the Marshall Plan andthe containment doctrine are analysed. Western European countries’ actionsin the field of security are also taken into account, because the commitmentof the United States to defend Europe was dependent on the developmentof cooperation in this area by the Europeans themselves. This cooperationwas reflected in the Treaty of Dunkirk signed by the United Kingdom andFrance in 1947 and in the Treaty of Brussels signed a year later by the UnitedKingdom, France, Belgium, the Netherlands and Luxembourg, which led tothe creation of the Western Union. The main problems that emerged duringthe North Atlantic Treaty negotiations and their resolution within the frameworkof the Transatlantic bargain, which is the basis of NATO's functioning,are also analysed.
Keywords: NATO, Cold War, Soviet expansionism, policy of containment, Truman Doctrine, Marshall Plan, security of Western Europe, Treaty of Dunkirk, Treaty of Brussels, North Atlantic Treaty